Change management as a tool for sustainable development of tourism organizations in Ukraine in the context of European integration - Pushak, Y.; Pidhirna, V.; Zybareva, O. (Економічний вісник Донбасу, 2025)
The development of the tourism sector is one of the key factors of economic growth and Ukraine’s integration into the European space. Tourism performs not only an economic but also a socio-cultural function, contributing to the formation of a positive national image and the promotion of intercultural dialogue. In the context of the crisis challenges of recent years – the COVID-19 pandemic and the full-scale war – issues of effective management and change management in tourism organization have become particularly relavant. The purpose of the article is to analyze the characteristics of adaptation processes in Ukrainian tourism organizations during 2020–2023, identify key directions of transformation, and determine prospects for further development in the context of European integration. The paper outlines the theoretical foundations of change management presented in the works of foreign and domestic scholars (K. Lewin, J. Kotter, Z. Bauman, J. Baudrillard, J. Urry, V. Kyfiak, O. Liubitseva, etc.). It is noted that the modern tourist combines the desire for comfort and safety with the need for new experiences, which creates a balance between authenticity and convenience and influences the managerial strategies of tourism companies. A statistical analysis of tourism development is presented: in 2020, international arrivals declined by 74%; in 2022–2023, recovery reached 65–84% of the 2019 level. In Ukraine, in 2023, employment in the hotel and restaurant sector decreased to 61.5 thousand persons, while the balance of enterprises declined by more than UAH 4 billion compared to 2021. The article demonstrates that the key adaptation mechanisms included digitalization (online platforms, CRM systems, mobile applications), reorientation toward domestic tourism (its share increased to 65–70%), marketing innovations, human resource transformations, and flexible employment models. At the same time, unresolved problems were identified: workforce losses, insufficient financial support for small and medium-sized enterprises, and a weak institutional framework. In the post-war recovery perspective, priority areas of change management include infrastructure modernization, development of domestic tourism as an economic and social resource, digital transformation, and the formation of a positive international image of the state. The experience of EU countries, particularly Romania, proves the effectiveness of integrated strategies that combine institutional support, public-private partnerships, and innovative management practices. Розвиток туристичного сектору є одним із ключових факторів економічного зростання та інтеграції України в європейський простір. Туризм виконує не лише економічну, а й соціально-культурну функцію, сприяючи формуванню позитивного національного іміджу та просуванню міжкультурного діалогу. У контексті кризових викликів останніх років – пандемії COVID-19 та повномасштабної війни – питання ефективного управління та управління змінами в туристичній організації набули особливої ​​актуальності. Метою статті є аналіз особливостей адаптаційних процесів в українських туристичних організаціях протягом 2020–2023 років, визначення ключових напрямків трансформації та визначення перспектив подальшого розвитку в контексті європейської інтеграції. У статті викладено теоретичні основи управління змінами, представлені в працях зарубіжних та вітчизняних науковців (К. Левін, Дж. Коттер, З. Бауман, Ж. Бодрійяр, Ж. Уррі, В. Кифяк, О. Любіцева та ін.). Зазначається, що сучасний турист поєднує прагнення до комфорту та безпеки з потребою в нових враженнях, що створює баланс між автентичністю та зручністю та впливає на управлінські стратегії туристичних компаній. Представлено статистичний аналіз розвитку туризму: у 2020 році кількість міжнародних прибуттів скоротилася на 74%; у 2022–2023 роках відновлення досягло 65–84% від рівня 2019 року. В Україні у 2023 році зайнятість у готельно-ресторанному секторі зменшилася до 61,5 тис. осіб, тоді як залишки підприємств скоротилися більш ніж на 4 млрд гривень порівняно з 2021 роком. У статті показано, що ключовими механізмами адаптації були цифровізація (онлайн-платформи, CRM-системи, мобільні додатки), переорієнтація на внутрішній туризм (його частка зросла до 65–70%), маркетингові інновації, трансформація людських ресурсів та гнучкі моделі зайнятості. Водночас було визначено невирішені проблеми: втрати робочої сили, недостатня фінансова підтримка малих та середніх підприємств, слабка інституційна база. У перспективі післявоєнного відновлення пріоритетними напрямками управління змінами є модернізація інфраструктури, розвиток внутрішнього туризму як економічного та соціального ресурсу, цифрова трансформація та формування позитивного міжнародного іміджу держави. Досвід країн ЄС, зокрема Румунії, доводить ефективність інтегрованих стратегій, що поєднують інституційну підтримку, державно-приватне партнерство та інноваційні практики управління.